Secretome of Staphylococcus aureus - Liew, Yun Khoon; Neela, Vasantha Kumari (Academic Journals, 2010)
Presence of secreted proteins is the key for sustenance of Staphylococcus aureus strains in the host system. General secretory (Sec) system is a well known and major secretion system that is responsible for the transportation of exoproteins across the bacterial cytoplasmic membrane and cell wall. In order to define the secretome of S. aureus, the availability of combination of two-dimensional gel electrophoresis (2-DE) with the latest advanced techniques (MALDI-TOF and ESI-MS/MS) has provided a powerful tool for the investigation of a large number of protein spots with the aim of identifying new drug candidates and discovering new diagnostics tools. In this paper, we present a short review regarding S. aureus general secretory system and role of secreted protein in host cells, and discuss the proteomic, together with genomics of S. aureus.